SQL functions programmer’s reference - Jones, Arie; Stephens, Ryan K; Plew, Ronald R; Garrett, Robert F; Kriegel, Alex (Computer program language, 2005)
* Gives programmers two-in-one coverage, with both a "how-to" on SQL functions and a complete SQL functions reference * SQL is the standard language for database queries; this book's advanced coverage helps programmers write their own SQL functions * Covers both the internationally standardized SQL 99 functions and the hundreds of additional functions introduced by vendors, including the subtle variations required to successfully migrate or interoperate between vendor products * Covers the latest versions of the major relational database management system (RDMS) applications: Microsoft SQL Server, Oracle, IBM DB2, and MySQL